2004
DOI: 10.1097/00042737-200411000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and grading of gastritis by non-invasive optical analysis

Abstract: The results show that, in a normal clinical setting, the optical in vivo analysis provided by our system detects alterations typical of gastritis, and allow for their graded scoring with a specificity and sensitivity that compare well with those of standard histology, while avoiding the invasiveness of the latter procedure. The method is adaptable to the screening of other types of lesions and mucosae and, hence, should prove useful in improving available diagnostic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The gastrointestinal tract, forming an ideal dark environment, can be explored by reflectance and AF analysis techniques. By spectrophotometry, Charvet et al have shown that reflectance analysis is able to better identify pathological mucosa than endoscopic examination [3]. In a previous study, we demonstrated for the first time that multispectral imaging is capable to detect reflectance modifications at specific wavelengths on visible spectrum, associated with gastric inflammation, both in a mouse model and in human [4].…”
Section: Introductionmentioning
confidence: 77%
“…The gastrointestinal tract, forming an ideal dark environment, can be explored by reflectance and AF analysis techniques. By spectrophotometry, Charvet et al have shown that reflectance analysis is able to better identify pathological mucosa than endoscopic examination [3]. In a previous study, we demonstrated for the first time that multispectral imaging is capable to detect reflectance modifications at specific wavelengths on visible spectrum, associated with gastric inflammation, both in a mouse model and in human [4].…”
Section: Introductionmentioning
confidence: 77%
“…35–38 We have already shown hat the determination of these optical coefficients enable minimal alterations of skin surface to be detected in an experimental murine model, 26 and can also correctly evaluate human mucosa in patients undergoing gastroscopy for suspected gastritis alterations. 20 Here, we have tested whether the procedure can also be used to detect alterations of the vulvar epithelium, including VIN, vulvitis and lichen sclerosis. We have further assessed whether the method has a sufficient sensitivity to become a useful complement of standard clinical diagnosis, while limiting the need for an invasive biopsy for histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 19 We have found that this equipment allows for an in vivo , real-time detection of minimal tissue lesions, like those expected at the beginning of inflammatory and cancerous alterations. 15 , 20 Here we have assessed whether the method has a sufficient sensitivity to identify alterations of vulvar tissues in patients undergoing vulvoscopy. We report that the Optiprobe method discriminated normal and pathological cases, with a sensitivity and specificity that compared well with those of histological analysis, while avoiding the need of invasive biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cellular architecture as well as the biochemical compounds embedded in the tested tissue sample, these parameters provide valuable histological information that can be effectively used for staging and grading precancerous/ cancerous tissue lesions. Such a technique, aimed at characterizing these optical properties within small tissue volumes of approximately 1 mm 3 by carrying spatially-spectrally resolved reflectance measurements, has been introduced (6,7) and successfully used through the instrument channel of an endoscope for grading gastritis (8). The development of MEMS with spectrometric capabilities would certainly benefit the development of endoscopic instruments using such non-imaging optical measurement modalities.…”
Section: Non-imaging Endoscopic Techniquesmentioning
confidence: 99%